2020
DOI: 10.1002/ejic.202000906
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Isophthalate Metal‐Organic Frameworks: Crystal Structure, Thermal Behavior, and White Luminescence

Abstract: Two novel lanthanide metal-organic frameworks (LnMOFs), Ln 1.14 Na 0.57 (BDC) 2 (H 2 O) • 4H 2 O (Ln=La 3 + or Ce 3 + , BDC : 1,3-benzenedicarboxylate), have been synthesized under hydrothermal conditions by using a Ln 3 + coordination polymer as precursor. The crystal structure was determined from single crystal X-ray diffraction. Both compounds are isostructural and contain chains of face-sharing [LnO 10 ] polyhedra connected by the linkers to form an anionic three-dimensional network, defining both polar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…The system was investigated for three different temperatures, 150, 160 and 170°C, and for four synthesis durations (5, 15, 30 and 60 min) (Figure 2). For a temperature of 150°C and whatever the synthesis time, the obtained phase corresponds to the precursor already reported in our previous work, [29] which actually is the initial white precipitate that one formed by adding the cationic solution to the basic solution of ligand. At 160°C, the LaMOF material is obtained only for a synthesis time of 60 min, for lower duration a mixture with precursor is obtained.…”
Section: Microwave Synthesissupporting
confidence: 59%
See 3 more Smart Citations
“…The system was investigated for three different temperatures, 150, 160 and 170°C, and for four synthesis durations (5, 15, 30 and 60 min) (Figure 2). For a temperature of 150°C and whatever the synthesis time, the obtained phase corresponds to the precursor already reported in our previous work, [29] which actually is the initial white precipitate that one formed by adding the cationic solution to the basic solution of ligand. At 160°C, the LaMOF material is obtained only for a synthesis time of 60 min, for lower duration a mixture with precursor is obtained.…”
Section: Microwave Synthesissupporting
confidence: 59%
“…The doped LaMOF material, namely LaMOF-5Eu-5Tb and LaMOF-7Eu-3Tb, where also prepared by microwave-assisted hydrothermal route at 170°C but the time duration was increased to 15 min to get pure phase. Both PXRD analysis (Figures S1 and S2) and FT-IR spectroscopy (Figure S3) confirmed the mixed Eu-Tb compounds are isostructural to undoped LaMOF [29].…”
Section: Microwave Synthesismentioning
confidence: 83%
See 2 more Smart Citations
“…1b, it can also be found that Zr-MOFs and Eu 5 @Zr-MOFs have almost the same vibrational absorption peaks as UiO-66, except the absorption peak at 1715 cm −1 from the CO stretching vibration of free carboxylate groups. 27,28 During the formation of Zr-MOFs, H 2 BDC ligands were replaced partially by m -H 2 BDC ligands with the free and active –COOH groups. The presence of unreacted and bare –COOH groups in Zr-MOFs leads to more pronounced absorption peaks at 1715 cm −1 than in UiO-66.…”
Section: Resultsmentioning
confidence: 99%